Indonesia’s Social Justice Indexes 2018 - Sujarwoto Sujarwoto; Andi Ahmad Yani; Asal Erlin Mulyadi; Dominggus Elcid Li (Indonesia Social Justice Network (ISJN), 2021)
We proposed measurement for Indonesia’s Social Justice Indexes (ISJI). Based on proposal, we calculated the indexes using national representatives’ surveys data and official public statistics. We adopted Alkaire Multidimensional Poverty measure to calculate the indexes. The score of social justice indexes of Indonesia in 2018 was 63.46. We confirmed that that citizens in Papua, West Papua and East Nusa Tenggara were the lowest among 34 provinces across archipelago. Addressing inequality of social justice development was critical for Indonesia development now and in the future. Abstrak Kami membuat indeks keadilan sosial Indonesia dan menghitung skor indeks keadilan sosial di 34 provinsi di Indonesia dengan menggunakan data yang bersumber dari beberapa survei nasional dan laporan statistik lembaga pemerintah. Kami menggunakan formula penghitungan kemiskinan multidimensional yang dibuat oleh Alkaire dkk. Hasil penghitungan indeks keadilan sosial Indonesia 2018 adalah 63.64. Skor indek terendah ada di Provinsi Papua, Papua Barat dan Nusa Tenggara Timur. Menghapus/mengurangi ketimpangan dalam pembangunan keadilan sosial adalah isu krusial dalam pembangunan Indonesia saat ini dan masa-masa yang akan datang.